Sustainable Design Approaches for Handicraft Community Development in Machakos County. - Muiya, Michael K. (Machakos University, 2018)
This paper highlights the important role played by design in shaping the new African continent economically, socially and environmentally. This role is highly linked to the rich interaction between religion, art and culture in Africa. Africa thrives well through networks formed by different cultures, customs, history and people spirit of working together. It is in such setups that handicrafts communities thrives well, however, Africa has been left behind in the sustainability of the practice key to rural development. This paper is aimed at exploring ways in which design can play a key role in the process of developing sustainable handicraft communities from inception to full implementation. It also explores the barriers for the uptake of community development initiatives in the design profession in Africa. Qualitative analysis and case studies are the major research strategies used. Wamunyu area will be used as the case study of a handicraft community existing in Machakos County. Data collected from archives, interviews and published reports for this purpose. This paper concludes that design plays an important role in the development of sustainable handicraft communities especially in the rural areas. The impact of this research is realized by the benefits of sustaining the handicraft communities that are important enterprises in rural areas development. The innovative use of design approaches today ensures a smooth transition for design use in Africa’s problems tomorrow. Key words; Community development, Design approaches, Handicrafts, Sustainability.
Keywords: Community development